Prevalence of Various Eye Diseases in Blind School Children - Aneeq Ullah Baig Mirza, Azeem Arif, Naheed Ghani (Journal of Rawalpindi Medical College, 2009)
Background: .To study the causes of visual disability and severity of blindness in blind school children and to document the effect of consanguinity of marriages on the visual health of the off springs. Methods: A study of female children belonging to a blind school in interior Lahore was carried out. 49 girls belonging to the particular school were examined in detail at a tertiary care hospital (Jinnah Hospital, Lahore). The evaluation included detailed history, general physical examination, visual acuity, slit lamp examination for anterior segment and direct as well as indirect ophthalmoscopy for posterior segment pathologies. Results: Age range was 3-15 years (mean 11, median 12 and mode 14years). 90.8% had blindness and 9.2% had visual impairment. Retinal disease was seen in 50%, globe disorder in 29.6% and cataract-related problems & buphthalmos in 11.22% of cases. Complex microphthalmos (the main contributor to globe disorders) was present in 20 eyes (20.40%) and simple microphthalmos was seen in 2 eyes (2.0%). Other globe disorders were anterior staphyloma, phthisis bulbi and anophthalmos. History of prior surgical treatment was noted in 13 eyes. 57.1 % had high consanguinity. Among Retinitis Pigmentosa (RP) patients, 15 (68.18%) had history of first cousin marriage (of their parents). None of the parents were affected phenotypically. Conclusion: Retinitis pigmentosa was the major contributor to childhood blindness, followed by globe disorders, lens related problems, buphthalmos and others. High consanguinity was detected in family history especially those involving retinitis pigmentosa.